2013
DOI: 10.1051/e3sconf/20130132010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of anthropic influences in an estuarine system of Southeastern Brazilian Coast by applying enrichment factors

Abstract: Abstract. This study presents an evaluation of metals and As deposition in the Bertioga Channel (Santos Region, Southeastern Brazilian coast) along the last 150 years, which corresponds to the main anthropogenic activity in the area. The studied area is located in the so-called Baixada Santista, where the main Brazilian harbor and one of the most important industrial centers of the country are located. This work consisted of sampling five sediment cores along this channel. The cores were sliced every 2 cm, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 2 publications
1
5
0
Order By: Relevance
“…Few samples showed some signs of contamination and all of them were located near the Cubatão Industrial Complex, which is in agreement with the EF values reported by Bordon et al (2011). Arsenic showed significant correlation but less Pearson's correlation coefficient when compared with the others, maybe because it is a metalloid, different from the others, and might have naturally enriched occurrence on the Brazilian shelf sediment (Mirlean et al, 2012;Gonçalves et al, 2013), indicating that some samples may not be directly enriched by human activity. The SQGs are based on the comparison with values that could cause deleterious effects on the biological community; these are quite simple to use and easy to understand.…”
Section: Valores Guia De Qualidade (Sqg)supporting
confidence: 85%
See 3 more Smart Citations
“…Few samples showed some signs of contamination and all of them were located near the Cubatão Industrial Complex, which is in agreement with the EF values reported by Bordon et al (2011). Arsenic showed significant correlation but less Pearson's correlation coefficient when compared with the others, maybe because it is a metalloid, different from the others, and might have naturally enriched occurrence on the Brazilian shelf sediment (Mirlean et al, 2012;Gonçalves et al, 2013), indicating that some samples may not be directly enriched by human activity. The SQGs are based on the comparison with values that could cause deleterious effects on the biological community; these are quite simple to use and easy to understand.…”
Section: Valores Guia De Qualidade (Sqg)supporting
confidence: 85%
“…There is no specific source for As in the region, which indicates enrichment not directly related to anthropogenic actions, as none of its levels were above Level 1 from CONAMA 454/2012. Furthermore, Gonçalves et al (2013) noticed that the enrichment followed the trends of the Santos Harbor growth in 1892 and the local rainy and dry seasons. Harbor and urban construction activities, dredging, and discharge of wastes may cause changes in the sedimentological pattern, and consequently disrupt the processes of weathering and sedimentation by acting on the rocks naturally enriched in As.…”
Section: Valores Guia De Qualidade (Sqg)mentioning
confidence: 86%
See 2 more Smart Citations
“…We recommend marking individuals released with plastic or transmitter for the assessment of the real post-released survival of these animals. Furthermore, as Bertioga is a region with high anthropogenic impact (Gonçalves et al, 2013), studies on contaminants and the impact of climate change are needed. On the one hand, the premature abandonment of newborns can hinder survival, exposing them to severe predation pressure (Springer, 1967) and energy challenges that they are not ready to deal with yet.…”
Section: Discussionmentioning
confidence: 99%